Locomotion traces emplaced by modern stalkless comatulid crinoids (featherstars) - Myers, Reed A.; Furlong, Carolyn M.; Gingras, Murray K.; Zonneveld, John-Paul (My University, 2023)
Modern crinoids have the ability to use their arms to crawl along the sea floor and some are capable of swimming short distances. The first and only evidence of crinoid locomotion reported from the rock record was described from the Middle Jurassic of the Cabeço da Ladeira Lagerstätte (Portugal) resulting in description of the ichnotaxon Krinodromos bentou. Although the mechanics of crinoid movement are well documented the morphological ranges of crinoid motility tracks are unknown. This study uses observations of crinoid movement and their effects on sediment using modern comatulid crinoids to propose possible trace fossil morphologies. Using 20 experimental trials supported by photography, video analyses, 3D orthogrammetry and resin casting, the morphological ranges of crinoid motility tracks are included in five distinct morphologies attributed to ambling, crawling, walking, running, and landing/taking-off traces, the latter of which are emplaced before and after swimming. Traces produced by ambling occur as epigenic hook-shaped grooves. Crawling traces comprise closely spaced hook-shaped grooves and ridges preserved in concave and convex epirelief. Walking traces consist of semi-bilaterally symmetrical collections of three or more grooves, and associated ridges, preserved in convex and concave epirelief. Running traces consist of semi-bilaterally symmetrical collections of one to three straight to semi-sinusoidal grooves and associated ridges preserved in concave and convex epirelief. Landing/taking-off traces are mounded features preserved in convex epirelief, with grooves radiating from the center. The five trace types described in this paper provide insight into morphological features that can be associated with modern crinoid activities and used to identify crinoid trace fossils, which are rarely reported, in the rock record.
Keywords: Crinoidea; Crinozoa; Echinodermata; experimental studies; ichnofossils; laboratory studies